Dose effects in behavioural treatment of post-stroke aphasia: a systematic review and meta-analysis. Issue 12 (5th June 2022) - Harvey, Sam; Carragher, Marcella; Dickey, Michael Walsh; Pierce, John E.; Rose, Miranda L.
Abstract: Purpose: Aphasia is a debilitating chronic acquired language disorder that impacts heavily on a person's life. Behavioural treatments aim to remediate language processing skills or to enhance communication between the person with aphasia and others, and a number of different treatments are efficacious. However, it is unclear how much of a particular treatment a person needs in order to optimise recovery of language and communication skills following stroke. Materials and methods: Systematic search for and meta-analysis of experimental studies that directly compared different amounts of the same behavioural aphasia treatment, following PRISMA guidelines. Results: Treatment dose research in aphasia is an emerging area. Just six studies comparing different doses of the same intervention met all criteria for inclusion. Evidence from these studies was synthesised and meta-analysed, where possible. Meta-analyses were inconclusive due to limited data; however, there are indications that suggest increased dose may confer greater improvement on language and communication measures, but with diminishing returns over time. Aphasia severity and chronicity may affect dose–response relationships. Conclusions: There is currently insufficient evidence to determine the effect of dose on treatment response. A dedicated and coordinated research agenda is required to systematically explore dose–response relationships in post-stroke aphasia interventions. A video abstract is available in the Supplementary Material . Implications for rehabilitation: The investigation of the effect of dose on treatment outcomes in post-stroke aphasia is an emerging research area with few studies reporting comparison of different amounts of the same intervention. In the acute phase of recovery following stroke, higher doses of treatment provided over short periods may not be preferable, tolerable, or superior to lower doses of the same treatment. In the chronic phase, providing additional blocks of treatment may confer additional benefit for some people with aphasia but with diminishing returns. People with chronic aphasia can achieve and maintain significant gains in picture naming after a relatively brief period of high-dose treatment.